Analysis of differences of running performences of elite european and latin american football players - Ademovic, A.; Palic, A.; Colakhodžic, E.; Popo, A. (Sports Science and Health, 2021)
This research is aimed to determine the differences in the racing performances of elite European and Latin American footballers. The research was conducted on a sample of N = 157 top football players, aged 19 to 35, who played all 90 minutes in the first round of the group stage of the competition at the 2018 World Cup. Respondents were classified into two groups, where group I (N = 103) consisted of football teams from Europe, and group II (N = 54), consisted of teams from Latin America. The obtained data showed that 8 out of 13 variables have the characteristic of heterogeneity with a higher value of variance than the arithmetic mean. The results of the T-test showed that only 4 of 13 variables had statistically significant differences. Footballers from European national teams are on average taller than Latin American footballers by just over 3 cm. European footballers had a 4% greater (p> 0.05) total distance traveled, distance in the first and second half of the game than Latin American footballers.